Determination of Sunscreen Gel’s SPF (Sun Protecting Factor) Value Containing Cemba Leaf Extract (Acacia rugata (Lam.) Fawc. Rendle) - Muzayyidah, Muzayyidah; Sukara, Muhammad Akmal A; Syahrianti, Andi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Excessive sun exposure can have negative effects on the skin. One way to reduce this impact is to use sunscreen. This study aims to formulate cemba leaf ectract into a stable sunscreem gel preparation and to determine the resulting sun-protecting factor (SPF) value. Using the laboratory experimental method, cemba leaves were extracted using the maceration method and the extract was made as an active ingredient in a gel preparation with concentrations of each formula including 0.5% (F1), 1% (F2), and 1.5% (F3). The gel preparation that had been made was then tested for stability using the cycling test method at temperatures of 4oC and 40oC. The research results of the cemba leaf extract gel preparations showed good stability and met the quality requirements in term of organoleptic, homogeneity, pH viscosity, spreadability, and adhesiveness with no significant difference before and after the cycling test (p<0.05). Determination of SPF value using UV-Vis spectrophotometry obtained the values of each formula respectively are 31.99 (F1), 43.23 (F2), and 43.24 (F3). The three formulas show activity as sunscreen seen from the SPF value > 15 which is included in the ultra-category.